Photodegradation of Remazol Yellow Using A-Type Zeolite/TiO2 - Tumbel, Elsa D.; Wuntu, Audy D.; Abidjulu, Jemmy (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2015)
The research aimed to study photodegradation of remazol yellow (RY) using TiO2-impregnated A-type zeolite (zeolite-A/TiO2) has been conducted. The materials having zeolite/TiO2 ratio of 1:0.2, 1:0.4, 1:0.6, 1:0.8, 1:1.0, 1:1.2, dan 1:1.4 g/g were used to degrade remazol yellow (RY) under ultraviolet irradiation for 3 hours and percentages of RY degraded were determined using spectrophotometer at 414 nm. Those with zeolite/TiO2 ratio of 1:0.2, 1:0.8, and 1:1.2 were used to study photodegradation kinetics at time range up to 3 hours. The results showed that the highest amount of RY degraded (82.17%) was attained by the use of material with zeolite/TiO2 ratio of 1:0.2. This material generated the highest value of rate constant (k=0.074 min-1), followed by those of 1:1.2 (0.045 min-1) and 1:0.8 (0.025 min-1).